Who are the future seaweed consumers in a Western society? Insights from Australia. Issue 2 (4th February 2019) - Birch, Dawn; Skallerud, Kåre; Paul, Nicholas A.
Abstract : Purpose: The purpose of this paper is to profile the consumers who are likely to eat seaweed products in Australia. Design/methodology/approach: The study was conducted as an online survey among 521 Australian consumers. Binary logistic regression modelling was used to profile the consumers. Findings: The paper identifies education, familiarity, food neophobia (FNeo), symbolic value of food consumption, health consciousness, as well as snacking behaviour as significant predictors of likelihood to eat seaweed products. Consumers with a university degree (i.e. undergraduates and postgraduates) are four times more likely to eat seaweed products, and those familiar with seaweed products have a 7.6 higher likelihood to eat seaweed products. FNeo makes the largest contribution to the consumer's likelihood to eat seaweed. A one unit increase in the FNeo score is associated with a 77 per cent decrease in the predicted odds of eating seaweed products in the next 12 months. The symbolic value of food consumption and health consciousness both doubled the likelihood of eating seaweed products. Snacking behaviour increases the likelihood by 185 per cent. The study reveals that early adopters of seaweed food products in western societies are people with higher educational levels, who are adventurous in their food choices and perceive seaweed consumption to have symbolic value. They are also health conscious "snackers". Originality/value: This study is one of the first attempts to provide insights about consumption of seaweed products; and also reveals the consumer groups in western societies that are most likely to eat seaweed products and who can be targeted as potential early adopters.